Media image of cultural and social conditions in Slovakia in 1939-1945 - Benčič Stanislav; Križan Adam (Research Retrieval and Academic Letters, 2025)
The article deals with the analysis of cultural development in Slovakia during 1939-1945, when the country was undergoing significant political and social changes as a result of the establishment of the Slovak state and the Second World War. At this time, culture was strongly influenced by the ideological pressures of the regime, which used cultural activities to disseminate propaganda and consolidate national identity by official ideology. The authors examine the mechanisms of censorship, access to Jewish culture during the Holocaust, and the role of important cultural institutions and personalities. The article also reflects on the consequences of wartime events on the creation and functioning of cultural life, highlighting the decline, ideological manipulation, and losses in the field of artistic creation. The study’s results highlight the complex relationship between politics and culture in the totalitarian regime and its long-term impact on the Slovak cultural landscape.